REKAYASA KOLEKTOR SURYA DAN KOMPOR LPG PADA PENGOVENAN DAUN TEMBAKAU VIRGINIA - SAMSURI TIRTOSASTRO; DARMONO DARMONO; SUBANDI SUBANDI (Jurnal Penelitian Tanaman Industri, 2000)
Engineering of solar collector and LPG-burner for curing Virginia tobaccoIndonesia produces 30 tones of Hue cured tobacco every year. Curing Virginia tobacco needs I 29 I kerosene per I kg cured leaves, thus lo process 30 tones cured leaves, it needs 38.7 liter kerosene with a value ol Rp 1 5.5 billion per year Kerosene as a source of energy is used for house hold in Ihe village and it is highly subsidized by the government. For such industries as tobacco processing other sources of energy are available, including gas oil, diesel oil and fuel oil, solar energy, coal, and liquid petroleum gas This study was aimed at designing solar collector and LPG buner suitable lor Virginia tobacco flue curing. Tobacco leaves were cured in a curing barn with LPG as a fuel, while the solar collector was installed on Ihe roof of Ihe barn. The size of the curing barn was 4 m x 4 m x 7 m with a capacity of iwo tones fresh leaves. The LPG-burner used was BA'I'/Baliltas-I, with was specially designed for lobacco curing barn ('nring method followed Ihe standard method practiced by farmers The experiment was conducted al IT Sadhana Arif Nusa. Has! Lombok. NTR from Angus! lo September 1997 The rcsull of experiment was evaluated holh from technical and economical aspects. The used of LPG combined with solar collector as the source of energy could reach Ihe required temperatures (J0-70°(.) during curing phases LPG consumption was 0.86 kg/ kg cured leaves, and solar energy contributed 6.48% of total energy required for curing process From economical view, the used of LPG and solar energy was not profitable. This was mainly due to Ihe high prices of LPG (Rp I 000 /kg) LPG-lank (Rp 1 600 000/unit) and roof- solar collector (Rp I 500 000 per unit).